2018
DOI: 10.1016/j.palaeo.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Crvenka loess-paleosol sequence: A record of continuous grassland domination in the southern Carpathian Basin during the Late Pleistocene

Abstract: In this study, we compare two independent paleoenvironmental proxies for a loess sequence in northern Serbia, in the southern Carpathian Basin: novel n-alkane biomarkers and traditional land snail assemblages. Both are associated with other, more widely used proxy data for loess sections, such as environmental magnetism, grain size, and geochemical indices. Together, these paleoenvironmental proxy records provide evidence for the continued dominance of grasslands during the Late Pleistocene in the Southern Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 88 publications
(200 reference statements)
4
30
0
7
Order By: Relevance
“…Similar stable semi-arid conditions have been discovered to have occurred in the Late Pleistocene paleoclimatic and paleoenvironmental records in the region of Vojvodina [72]. The last glacial loess snail fauna in the investigated area, which is characterized by a complete absence of any cold-resistant species, suggests a stable, dry, and relatively warm glacial summer climate, when compared to other European loess provinces [35,[73][74][75].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar stable semi-arid conditions have been discovered to have occurred in the Late Pleistocene paleoclimatic and paleoenvironmental records in the region of Vojvodina [72]. The last glacial loess snail fauna in the investigated area, which is characterized by a complete absence of any cold-resistant species, suggests a stable, dry, and relatively warm glacial summer climate, when compared to other European loess provinces [35,[73][74][75].…”
Section: Resultssupporting
confidence: 70%
“…Two independent, environmental pieces of evidence from this loess-paleosol section, novel n-alkane biomarkers and traditional land snail assemblages, independently confirm a relatively stable paleoenvironment during the past 150 kyr. One characterized by the continuous dominance of grassland vegetation, with periodic intervals involving forest elements [72]. Using stable carbon isotopes (δ13C) of organic matter in reconstructing Quaternary climate variability based on loess are widely used methods and the most important factors controlling the isotopic signal in soils and sediments implying the changes in the photosynthetic pathway (shifts from C3 to C4 vegetation), physiological water stress, and changes in the atmospheric CO 2 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Conclusions comparable to the ones reached in this study can be found in various paleoclimate studies [36], suggesting that aridity in the investigated region is not characteristic only for the recent climate, but was also common in past geological periods. Many analyzed paleoclimatic proxies related to the last glacial loess also report a periodic [36,79,80] or even continuous presence of arid climate conditions [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as the MIS 6 stage is considered to be one of the most climatically severe periods in Europe, with the farthest extent of the glaciers (Ehlers and Gibbard, 2007; Francke et al ., 2016). The glacial action producing the sediment, increased fluvial and aeolian transport, in combination with a cold and dry climate and predominantly dry steppe and/or forest steppe‐like conditions (Marković et al ., 2006, 2007, 2018) supports increased sediment availability in the system.…”
Section: Resultsmentioning
confidence: 86%